2021
DOI: 10.1038/s41598-021-92975-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel strategy for site selective spin-labeling to investigate bioactive entities by DNP and EPR spectroscopy

Abstract: A novel specific spin-labeling strategy for bioactive molecules is presented for eptifibatide (integrilin) an antiplatelet aggregation inhibitor, which derives from the venom of certain rattlesnakes. By specifically labeling the disulfide bridge this molecule becomes accessible for analytical techniques such as Electron Paramagnetic Resonance (EPR) and solid state Dynamic Nuclear Polarization (DNP). The necessary spin-label was synthesized and inserted into the disulfide bridge of eptifibatide via reductive fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Similar approaches were used on a LecA protein interacting with galactose linked to TOTAPOL, and dihydrofolate reductase (DHFR) interacting with its ligand trimethoprim (TMP) covalently linked with TOTAPOL . However, in these cases, significant NMR signal quenching may be encountered in the vicinity of the binding site. ,,,, Very recently, a method for insertion of a nitroxide spin label into disulfide bridges in proteins has been introduced . For membrane proteins, an approach where PAs are covalently bound to a lipid can be used; the reconstitution with such lipids allows a homogeneous incorporation of the PA into a membrane bilayer. , …”
Section: Sample Constitution For Biomolecular Dnpmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar approaches were used on a LecA protein interacting with galactose linked to TOTAPOL, and dihydrofolate reductase (DHFR) interacting with its ligand trimethoprim (TMP) covalently linked with TOTAPOL . However, in these cases, significant NMR signal quenching may be encountered in the vicinity of the binding site. ,,,, Very recently, a method for insertion of a nitroxide spin label into disulfide bridges in proteins has been introduced . For membrane proteins, an approach where PAs are covalently bound to a lipid can be used; the reconstitution with such lipids allows a homogeneous incorporation of the PA into a membrane bilayer. , …”
Section: Sample Constitution For Biomolecular Dnpmentioning
confidence: 99%
“…98,156,158,329,330 Very recently, a method for insertion of a nitroxide spin label into disulfide bridges in proteins has been introduced. 331 For membrane proteins, an approach where PAs are covalently bound to a lipid can be used; the reconstitution with such lipids allows a homogeneous incorporation of the PA into a membrane bilayer. 332,333 Sani et al have utilized solid-phase synthesis to prepare a doubly spin-labeled variant of the antimicrobial peptide maculatin 1.1 (Mac1).…”
Section: Matrix-free Biomolecular Dnp Formulationsmentioning
confidence: 99%
“…DNP enhancement was demonstrated on the glycerol signals of the DNP matrix. Because eptifibatide was naturally abundant, and potentially subject to bleaching from the radical, it was not observed directly under the conditions of the experiment …”
Section: Strategies and Challengesmentioning
confidence: 99%
“…Because eptifibatide was naturally abundant, and potentially subject to bleaching from the radical, it was not observed directly under the conditions of the experiment. 156 As the indirect polarization pathway relies on spin diffusion, the degree of selectivity that targeted DNP can achieve is limited. In addition, the signal intensity of nuclear spins in the closest vicinity to the radical tag are strongly affected by bleaching effect due to paramagnetic relaxation enhancement (PRE) and may not be detectable in targeted approaches.…”
Section: Targeted Approachesmentioning
confidence: 99%
“…Herein, we demonstrate by high performance liquid chromatography (HPLC) and electrospray ionization mass spectrometry (ESI–MS) that the intercalator 2 can be incorporated into the disulfide bridge of the peptide. Recently it has been shown that eptifibatide can be efficiently spin-labeled for hyperpolarization applications employing Dynamic Nuclear Polarization 50 . In the present paper we demonstrate that it is also feasible to employ derivatives of eptifibatide as efficient hyperpolarization sources in PHIP-NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%